Volume 6: Polar and Arctic Sciences and Technology; Offshore Geotechnics; Petroleum Technology Symposium 2013
DOI: 10.1115/omae2013-10258
|View full text |Cite
|
Sign up to set email alerts
|

Improving MMP by Co-Injection of Miscible CO2 With Abu Dhabi Crude Oil

Abstract: Miscible CO2 injection is a method to increase oil production. Combinations of Carbon dioxide with other gases as miscible solvents are emphasized in this paper to improve CO2 miscible injection process. Emphasis is on identifying CO2 solvent mixtures with reduced MMP to achieve miscibility at reasonable injection pressures in Abu Dhabi fields. Two targeted crude oils (Oil 1 and Oil 2) from Abu Dhabi carbonate reservoirs are utilized. The minimum miscibility pressure (MMP) of targeted oils with mixtures of N2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They believe that ethane can also reduce MMP. For instance, Javid et al 88 predicted the MMP of the CO 2 -crude oil system after injecting nitrogen, methane, and ethane into two crude oil samples from the Abu Dhabi carbonate reservoir using the component simulation method. They found that ethane was more effective in reducing MMP, and the MMP of the first crude oil sample decreased by 100 psi/10 mol % after injecting ethane.…”
Section: Mmp Reducing Techniquesmentioning
confidence: 99%
“…They believe that ethane can also reduce MMP. For instance, Javid et al 88 predicted the MMP of the CO 2 -crude oil system after injecting nitrogen, methane, and ethane into two crude oil samples from the Abu Dhabi carbonate reservoir using the component simulation method. They found that ethane was more effective in reducing MMP, and the MMP of the first crude oil sample decreased by 100 psi/10 mol % after injecting ethane.…”
Section: Mmp Reducing Techniquesmentioning
confidence: 99%